Intention-based control for powered exoskeleton - Chou, Po Yang (2017)
Electromyogram is a technique to map a graph according to the activation signal of muscles. Intention-based control for power exoskeleton is aimed to allow operator to use exoskeleton with ease. Surface electromyogram (SEMG) sensor is used. When selected muscle contract, a motion is performed. In this project, it is focused on the “sit and stand” and “walking” motions. In walking motion, it is further broken down into stance phase and swing phase. Experiments were conducted to study the relationship between joint angles, by using IMU and motor angles, and SEMG signals. Finally, real-time experiments were conducted by combining the sensors to the exoskeletons. This report summarizes how SEMG signals are selected and used to trigger the exoskeleton.